Persistent vasovagal presyncope during follicular unit extraction hair transplantation: A case report - Lakshmiprasad Lakshmipathi; Mihir Shankar; Aniketh Venkataram; Venkataram Nagaraj Mysore (Journal of Hair Restoration and Regenerative Medicine, 2026)
Vasovagal reactions are well recognized during outpatient procedures; however, prolonged or persistent vasovagal episodes without frank syncope are less commonly described, particularly in hair transplantation. We report a patient who had persistent and recurrent giddiness and nausea for nearly 8 hours, which necessitated discontinuation of surgery, and the surgery could not be completed. A 45-year-old male undergoing follicular unit extraction (FUE) hair transplantation developed dizziness and nausea after graft harvesting and near completion of implantation, about 2 hours later from the start of the surgery. Despite stable vital signs, normal electrocardiogram (ECG), and appropriate supportive management, symptoms such as giddiness in the sitting position and nausea persisted for several hours, necessitating discontinuation of surgery. Ear, nose, and throat (ENT) evaluation ruled out benign paroxysmal positional vertigo and other peripheral vertigo. The patient recovered completely within 24 hours. The clinical picture was consistent with a persistent vasovagal episode with prolonged presyncope. This case highlights a less-recognized variant of vasovagal syncope— persistent vasovagal condition without syncope—during hair transplantation. Awareness of this entity is important, as symptoms may persist despite normal investigations and appropriate acute management.